Climate response to drastically modified PDO, PNA and NAM in the superinterglacial MIS 31 - Justino, Flávio; Gurjão, Carlos; Lindemann, Douglas (Boreas, 2022)
The Pacific Decadal Oscillation (PDO), the Pacific‐North American Pattern (PNA) and the Northern Annular Mode (NAM) influence the Northern Hemisphere climate over all sorts of time scales, from days to decades. This study evaluates these climate modes under drastically modified conditions. It is found that in Marine Isotope Stage 31 (MIS 31), an interglacial with enhanced seasonal amplitude, the PDO, PNA and NAM are completely different in their temporal and spatial patterns with respect to current conditions. Moreover, the MIS 31 boundary conditions induce an amplification of the interannual variability, but a suppression of the decadal peak. It is found that changes in the air–sea interaction in the NH, in particular due to a weaker Aleutian low, are responsible for the absence of the decadal periodicity. However, no large changes are verified in terms of explained variance of those modes with respect to CTR. However, the amplitude of response related to the PDO, NAM and PNA is weaker in the MIS 31 experiment, very likely due to a reduced meridional thermal gradient. The results presented here are useful for palaeoreconstruction interpretation because proxies may reproduce dominant characteristics of temperature and precipitation related to the persistence of those modes of variability. Thus, their ability to reproduce long‐term environmental conditions in some situations can be related to a preferential phase of the PDO, PNA and NAM.